The Incidence of Dental Caries in Children with Down Syndrome: A Systematic Review and Meta-Analysis - Mariana Martins; Paulo Mascarenhas; José Grillo Evangelista; Isabel Barahona; Vitor Tavares (MDPI AG, 2022)
Scientific evidence regarding the incidence of dental caries in Down syndrome (DS) patients is limited and sometimes presents divergent opinions among authors, making it difficult to reach definitive conclusions. We aimed to evaluate the caries incidence in the DS pediatric population and compare it against healthy controls. The search was performed using 4 universal databases: Cochrane, B-on, Biomed, and PubMed. The selected articles were synthesized and subsequently evaluated according to an adaptation of the Quality Assessment Checklist for Prevalence Studies risk of bias tool, and analysis charts were performed by the Risk of Bias visualization tool (ROBVIS). Statistics and graphs were performed by Open Meta Analyst and JASP software. The confounding effect on caries incidence of the following factors was evaluated through meta-regression: age, Male/Female (M/F) ratio, DMFT, dmft, and study geographic location. Overall, the incidence of caries in the DS population was 49.9%, whereas in the control population was 63.4%. The M/F ratio, DMFT, and dmft significantly affected the incidence of DS individuals (p-value < 0.05). The evidence regarding the lower pooled incidence of caries in individuals with DS regarding controls is limited by the few scientific reports available and cross-section designs. Therefore, further studies are needed to confirm these results.